Advisory opinion of ICJ: does it matter? - Mahmud Zuhdi Mohd Nor, (Fakulti Undang - Undang, 2001)
Hearing the requests for ‘advisory opinions’ is just one aspect of the judicial functions of the International Court of Justice (ICJ). Prior to the establishment of ICJ in 1945, the same jurisdiction also was provided for and exercised by the former World Court; the Permanent Court of International Justice which ceased to exist soon after the League of Nations perished. Looking at the very words ‘advisory opinions’ one may inadvertently underestimate the degree of importance of this special function. Despite its somewhat misleading character it can be proven that this type of judicial mechanism does exert some degree of legal binding nature against the parties to the requests. In fact, a lot of areas of law on the international plane have been affected as a result of the exercise of this judicial function. This paper looks at the legal nature of advisory opinions with reference to ICJ in the context of its achievements in the development of International law in specific areas of study